Management of Status Epilepticus, Refractory Status Epilepticus, and Super-refractory Status Epilepticus. Issue 2 (April 2022) - Trinka, Eugen; Leitinger, Markus
ABSTRACT: PURPOSE OF REVIEW: Status epilepticus is a serious condition caused by disorders and diseases that affect the central nervous system. In status epilepticus, hypersynchronous epileptic activity lasts longer than the usual duration of isolated self-limited seizures (time t1), which causes neuronal damage or alteration of neuronal networks at a certain time point (time t2), depending on the type of and duration of status epilepticus. The successful management of status epilepticus includes both the early termination of seizure activity and the earliest possible identification of a causative etiology, which may require independent acute treatment. In nonconvulsive status epilepticus, patients present only with subtle clinical signs or even without any visible clinical manifestations. In these cases, EEG allows for the assessment of cerebral function and identification of patterns in need of urgent treatment. RECENT FINDINGS: In 2015, the International League Against Epilepsy proposed a new definition and classification of status epilepticus, encompassing four axes: symptomatology, etiology, EEG, and age. Various validation studies determined the practical usefulness of EEG criteria to identify nonconvulsive status epilepticus. The American Clinical Neurophysiology Society has incorporated these criteria into their most recent critical care EEG terminology in 2021. Etiology, age, symptomatology, and the metabolic demand associated with an increasing duration of status epilepticus are the most important determinants of prognosis. The consequences of status epilepticus can be visualized in vivo by MRI studies. SUMMARY: The current knowledge about status epilepticus allows for a more reliable diagnosis, earlier treatment, and improved cerebral imaging of its consequences. Outcome prediction is a soft tool for estimating the need for intensive care resources.